Fuel consumption reduction by increasing thermal efficiency through heating of fuel / Edmund Hilary Nicholas ... [et al.] - Nicholas, Hilary Nicholas; Magaswaran, Kumaresan; Jayapal, Vikneswary (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2018)
The drive to produce a more efficient and low fuel consuming internal combustion engine has been ongoing ever since the birth of the internal combustion engine. This drive is ever so more important with the current stringent emission regulations all around the world. A complete burned fuel in an internal combustion engine produces lots of heat as a by-product. To convert this by-product into useful heat to increase efficiency is beneficial. This paper will investigate the potential of harvesting heat from the exhaust to preheat the fuel to improve fuel consumption. A heat exchanger is designed to heat up fuel followed by the experimentation on an internal combustion engine using various combinations of fuel temperature. Performance parameters such as thermal efficiency, exhaust gas, power, fuel consumption and output power are being discussed. The study shows that the fuel consumption is lowest at 34°C where else the maximum power was produced at 30°C.